2016
DOI: 10.1016/j.chemosphere.2016.01.125
|View full text |Cite
|
Sign up to set email alerts
|

A five-year performance review of field-scale, slow-release permanganate candles with recommendations for second-generation improvements

Abstract: In 2009, we identified a TCE plume at an abandoned landfill that was located in a low permeable silty-clay aquifer. To treat the TCE, we manufactured slow-release potassium permanganate cylinders (oxidant candles) that had diameters of either 5.1 or 7.6 cm and were 91.4 cm long. In 2010, we compared two methods of candle installation by inserting equal masses of the oxidant candles (7.6-cm vs 5.1-cm dia). The 5.1-cm dia candles were inserted with direct-push rods while the 7.6-cm candles were housed in screens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Previous results using SHMP with permanganate candles showed that it greatly minimized the formation of oxide coatings on the candle surface and facilitated a more consistent release of the oxidant from the candle (Christenson et al, 2016). Moreover, Chokejaroenrat et al (2013) found that SHMP also helped the oxidant penetrate low permeable zones in a series 2D-flow box experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results using SHMP with permanganate candles showed that it greatly minimized the formation of oxide coatings on the candle surface and facilitated a more consistent release of the oxidant from the candle (Christenson et al, 2016). Moreover, Chokejaroenrat et al (2013) found that SHMP also helped the oxidant penetrate low permeable zones in a series 2D-flow box experiments.…”
Section: Resultsmentioning
confidence: 99%
“…As an experimental treatment, sodium hexametaphosphate (SHMP) was included in some of the persulfate candle formulations by adding SHMP at 5% of the sodium persulfate weight. Adding SHMP to permanganate candles was previously found to improve oxidant release rates (Christenson et al, 2016). The persulfate candles were molded into the shape of a cylinder with a diameter of 1.3 cm and the length of 2.4 cm.…”
Section: Methodsmentioning
confidence: 99%
“…This aeration creates what is analogous to an airlift pump, where a circulation pattern is created that causes water to exist the top half of the screen and enter at the bottom. This induced flow pattern around the oxidant candle helps break the intermolecular forces holding the oxidant together and allows the oxidant molecules to solvate with water, thus preventing downward migration (Christenson et al, 2016(Christenson et al, , 2012 (Figs. SM-1 and SM-2).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of acetone and 2-butonone in one of the treatability studies and at one of the field sites prompted additional investigations to determine the source of the acetone. Methodologies used to manufacture the field-scale wax-based oxidant candles have previously been reported [17,25,27]. Supplementary Materials also contains detailed schematics of the oxidant delivery devices (Figure S2), direct-push installation procedures of the oxidant drive points, groundwater sampling and analysis methodologies, and the methods used to measure the longevity of the persulfate candles under field conditions.…”
Section: Treatability Studies Oxidant Manufacturing and Field-scale Installation And Sampling Proceduresmentioning
confidence: 99%
“…Kambhu et al [26] recently simulated these flow patterns by coupling a two-phase bubbly flow model with the Darcy flow model in a wide flow tank (Figure S1). By combining aeration with the slow-release oxidants, Christenson et al [25,27] created a continuous (i.e., 24 h per day, 7 days per week; 24/7) circulation pattern around each drive point, which over time, greatly facilitated the distribution of the oxidant to the target zone. Results from the initial field study showed that after more than seven years of deployment, the aerated oxidant candles were still functioning and had reduced downgradient TCE concentrations and associated contaminants by 90%.…”
Section: Introductionmentioning
confidence: 99%